Pharmacology and Pharmacoeconomics of Kombucha as a Functional Immunomodulatory Food for Children with Special Needs at Elementary School Level: Literature Review - Siti Jubaedah; Yugga Tri Surahman; Firman Rezaldi; Fahmi Alamil Huda; Erni Suminar; Syariful Mubarok (Jurnal Biologi Tropis, 2026)
Kombucha is a fermented tea-based beverage containing various bioactive compounds such as polyphenols, flavonoids, organic acids (acetic, gluconic, and glucuronic acids), and probiotic microorganisms produced by the Symbiotic Culture of Bacteria and Yeast (SCOBY). These compounds exhibit antioxidant, anti-inflammatory, and immunomodulatory activities that may support immune function. This study aimed to analyze the pharmacological and pharmacoeconomic aspects of kombucha as a functional immunomodulatory food for elementary-level children with special needs through a systematic literature review approach. Data were collected from Scopus-indexed journals and other reputable scientific databases published between 2016 and 2025. The findings indicate that kombucha exerts pharmacological effects by modulating pro-inflammatory and anti-inflammatory cytokines, enhancing antioxidant activity, and improving gut microbiota balance, thereby contributing to immune homeostasis. From a pharmacoeconomic perspective, kombucha shows potential as a cost-effective preventive functional food intervention with relatively low production costs and potential long-term healthcare cost efficiency. However, direct clinical evidence in children with special needs remains limited, highlighting the need for further experimental and clinical studies to establish safety, efficacy, and comprehensive cost-benefit evaluation.